2009
DOI: 10.1681/asn.2008060591
|View full text |Cite
|
Sign up to set email alerts
|

Age and Comorbidities Are Effect Modifiers of Gender Disparities in Renal Transplantation

Abstract: Women have less access to kidney transplantation than men, but the contributions of age and comorbidity to this disparity are largely unknown. We conducted a national cohort study of 563,197 patients with first-onset ESRD between 2000 and 2005. We used multivariate generalized linear models to evaluate both access to transplantation (ATT), defined as either registration for the deceased-donor waiting list or receiving a live-donor transplant, and survival benefit from transplantation, defined as the relative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
121
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 39 publications
(36 reference statements)
13
121
1
2
Order By: Relevance
“…12 In addition, our finding that older adults (despite excluding those with dementia) were less likely to report receiving KTPI even when they were informed according to their provider is consistent with the documented age disparity in referral and access to KT. 5,[13][14][15][16] In other words, older age is consistently associated with lack of access in all steps in the process to KT from provision of information to transplantation. Finally, whereas other studies have shown that provider-reported KTPI is associated with listing, 5 our study suggests a novel mechanism in which patient perception of KTPI is actually what drives the association between KTPI and listing.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, our finding that older adults (despite excluding those with dementia) were less likely to report receiving KTPI even when they were informed according to their provider is consistent with the documented age disparity in referral and access to KT. 5,[13][14][15][16] In other words, older age is consistently associated with lack of access in all steps in the process to KT from provision of information to transplantation. Finally, whereas other studies have shown that provider-reported KTPI is associated with listing, 5 our study suggests a novel mechanism in which patient perception of KTPI is actually what drives the association between KTPI and listing.…”
Section: Discussionmentioning
confidence: 99%
“…L iving donor kidney transplant (LDKT) is usually the best treatment option for kidney failure (1) but occurs less frequently among persons who are black or older (2)(3)(4). In 2007, blacks comprised only 13.8% of LDKT recipients in the United States-a percentage that has remained unchanged for 10 years (1).…”
mentioning
confidence: 99%
“…LDKTs also occur less frequently among older patients (2-4), whose anticipated waiting time for a DDKT often exceeds their life expectancy (6). In addition, several studies have reported decreased access to LDKTs among women (4,(7)(8)(9), although other studies have found no gender differences (2,3).…”
mentioning
confidence: 99%
“…One study reported that women have less access to transplant services. 17 At least 1 other failed to identify disparities in the likelihood of operative versus nonoperative management in relation to patient sex status. 1 Others have suggested better postsurgical outcomes for women following traumatic care, 13 although it is unclear whether this benefit extends to neurotrauma.…”
Section: Discussionmentioning
confidence: 99%